2017
DOI: 10.20396/bjos.v15i2.8648758
|View full text |Cite
|
Sign up to set email alerts
|

Parental age is related to the occurrence of cleft lip and palate in Brazilian populations

Abstract: Aim: To evaluate the association of environmental risk factors, particularly paternal and maternal age, with gender and type of oral cleft in newborn with nonsyndromic cleft lip with or without cleft palate (NSCL/P). Methods: This study included 1,346 children with NSCL/P of two Brazilian Services for treatment of craniofacial deformities. Parental ages were classified into the following groups: maternal age <35, 36-39, and ≥40 years; paternal age <39 and ≥40 years. The data was analyzed with chi-square test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
2
10
0
2
Order By: Relevance
“…Patients with orofacial clefts have additional risks of malnutrition and anaemia due to feeding problems 6 . Regarding mother's age, the majority were young, under the age of 29, a condition similar to that described in literature 13,22 . However, a study developed in Taiwan 18 found higher occurrence of cases of cleft lip and palate in mothers over the age of 35 years, but without statistical significance.…”
Section: Discussionsupporting
confidence: 78%
“…Patients with orofacial clefts have additional risks of malnutrition and anaemia due to feeding problems 6 . Regarding mother's age, the majority were young, under the age of 29, a condition similar to that described in literature 13,22 . However, a study developed in Taiwan 18 found higher occurrence of cases of cleft lip and palate in mothers over the age of 35 years, but without statistical significance.…”
Section: Discussionsupporting
confidence: 78%
“…Cleft palate alone is more common in women, while cleft palate and lip is more frequent among males, across various ethnic groups (20). In the present study, most children with clefts were males, corroborating similar results found in literature (2,(20)(21)(22)(23). Molecular and genetic studies are needed to better understand the differences between the types of oral clefts and gender (20).…”
Section: Discussionsupporting
confidence: 91%
“…This aligns with various studies that have reported increased congenital malformations in older parents. (6,15). A population-based study on Danish Facial Cleft Database, reported the influence of maternal and paternal ages on the risk of cleft lip with or without cleft palate increases with the advancing age of the other parent, and that the influence vanishes if the other parent is young.…”
Section: Discussionmentioning
confidence: 99%
“…Parental age has been proposed as a possible risk factor for OFC. (4) Previous studies conducted on the association between parental age and incidence of birth defects have yielded inconsistent results(5)(6,7). It is generally reported that advanced age may predispose chromosomes to irreversible changes and genetic alterations.…”
Section: Introductionmentioning
confidence: 99%